Impact of continuing folic acid after the first trimester of pregnancy: findings of a randomized trial of Folic Acid Supplementation in the Second and Third Trimesters. - MOLLOY, ANNE (My University, 2013)
BACKGROUND: Supplementation with folic acid (FA) is recommended worldwide before and during early pregnancy because of its proven effect in preventing neural tube defects, but the role of FA after the 12th gestational week (GW) is much less clear. OBJECTIVE: We investigated maternal folate and homocysteine responses and related effects in the newborn that resulted from continued FA supplementation after the first trimester of pregnancy. DESIGN: Pregnant women, aged 18-35 y, who were attending an antenatal clinic in Northern Ireland with singleton uncomplicated pregnancies and reported taking FA supplements in the first trimester, were randomly assigned at the start of trimester 2 to receive 400 μg FA/d or a placebo capsule. RESULTS: A total of 119 women (60 women in the placebo group; 59 women in the treatment group) completed the trial. From GWs 14-36, mean (±SD) serum folate decreased (from 45.7 ± 21.3 to 19.5 ± 16.5 nmol/L; P < 0.001) in unsupplemented women, whereas plasma homocysteine increased (6.6 ± 2.3 to 7.6 ± 2.3 μmol/L; P < 0.001). However, FA supplementation prevented these changes and resulted in a significant increase in red blood cell folate concentrations from 1203 ± 639 to 1746 ± 683 nmol/L (P < 0.001; GWs 14-36). Cord blood folate was significantly higher in the FA group than in the placebo group (red blood cell concentrations of 1993 ± 862 and 1418 ± 557 nmol/L, respectively; P = 0.001). CONCLUSIONS: Continued supplementation with 400 μg FA/d in trimesters 2 and 3 of pregnancy can increase maternal and cord blood folate status and prevent the increase in homocysteine concentration that otherwise occurs in late pregnancy. Whether these effects have benefits for pregnancy outcomes or early childhood requires additional study.
PUBLISHED
Keywords: folic acid (FA); folic acid (FA); International Development